Электрификация горно - обогатительных комбинатов: справочное пособие - Апенко В. П.; Богомолов Р. Е.; Бунько В. А.; Волотковский С. А.; Скляров М. И. (Москва, Недра, 1973)
Авт. указаны на обороте тит.